WORK STRESS AND ITS IMPACT ON THE PERFORMANCE OF AGRICULTURAL EXTENSION WORKERS IN NINEVEH GOVERNORATE - Talal Saeed Hameed; Osama Layth Mohammed Faeq (Jurnal Ekonomi, Bisnis dan Pendidikan, 2026)
The research was conducted in Nineveh Governorate and included all employees working in agricultural extension in the Directorate of Agriculture of Nineveh, and the research aims to identify the level of work pressures that affect workers in agricultural extension, identify the correlation between work pressures and each of the independent variables, identify the most important proposals that reduce the work pressures facing workers in agricultural extension. The research included (206) employees, including the sample of the initial test (pre-test) of (30) employees to extract stability, thus reaching the research community (176). A simple proportional random sample was selected by (50%) from the total population, so the final research sample is (88) employees. The data were collected through the questionnaire form, which consisted of two parts, the first of which included the independent variables of the respondents. The second part included a measurement to measure work pressure on workers in agricultural extension, which consisted of (22) items on the most important work pressures facing agricultural extension workers. The results showed that more than half of agricultural extension workers are exposed to work stress while working to a low degree. The variables (level of education, age, professional ambition) had a significant correlation with work pressures. Also, the proposal (increasing incentives and material and moral rewards) was a priority among the proposals proposed by the respondents.